Analisis Kesiapan Penerapan Rekam Medis Elektronik dengan Metode DOQ-IT: Narrative Review - Putra, Aji Wahyu; Sutha, Diah Wijayanti (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
By digitizing and integrating patient data, the Electronic Medical Records (EMR) initiative aims to increase the effectiveness and caliber of healthcare services. Using the DOQ-IT method, which encompasses a comprehensive evaluation of organizational support, change management, human resource competency, and technology infrastructure, this study seeks to assess Indonesia's preparedness for EMR implementation. This study reviews ten pertinent journals using a narrative review methodology. The analysis's findings indicate that a number of obstacles still stand in the way of Indonesia's EMR implementation preparedness, including inadequate infrastructure in rural regions, inadequate health worker training, reluctance to adapt, and a lack of specialized funding. However, the findings show that health facilities with strong managerial support and ongoing training programs have a better level of readiness. The DOQ-IT method has proven effective in providing a comprehensive picture of organizational readiness, although its implementation requires adaptation to the local context. By overcoming these obstacles through policy development, improving the competency of health workers, and improving infrastructure, comprehensive EMR implementation in Indonesia can be achieved.